Efficacy of the use of fractional CO2RE intima laser treatment in stress and mixed urinary incontinence. (January 2020) - Palacios, Santiago; Ramirez, Marieta
Summary: Objective: The objective of this clinical study was to evaluate the efficacy of a vaginal CO2 laser treatment (CO2RE Intima) in patients with moderate, severe and very severe stress urinary incontinence (SUI) or mixed urinary incontinence (MUI), as well as its impact in sexual relations. Design: This was a single-center, prospective, interventional study that included 25 women aged 35–68 years who presented with moderate, severe and very severe symptoms of SUI or MUI, based on Sandvik index and ICIQ-UI scores. A series of three fractional micro-ablative CO2 vaginal laser treatment sessions was performed, each spaced 4–6 weeks apart. Improvements were measured and evaluated using scores from validated questionnaires including the International Consultation on Incontinence Questionnaire (ICIQ-IU), the Sandvik severity index, and the Female Sexual Function Index (FSFI). Adverse events were recorded throughout the study and assessed using the Common Side Effect Questionnaire that evaluates pain, hemorrhage, burn, bruising and edema. Results: CO2RE intima laser treatment resulted in a significant improvement (P < 0.001) in the scores of both the ICIQ-UI questionnaire and the Sandvik index, after the 2 nd session; and this significance persisted after the 3 rd treatment session. Improvements in UI severity was also achieved; after the 1 st laser treatment, a significant improvement in severity was seen (p < 0.01), the significance of which showed to increase after the 2nd and 3rd treatment sessions (p < 0.001). Improvement related to the type of UI measured with the ICIQ questionnaire was significant in both cases with SUI (p = 0.035) and MUI (p < 0.001) after the second treatment. This difference persisted after the 3 rd treatment in cases of MUI and the trend, though not the statistical significance, persisted in SUI cases, (p = 0.197). Improvement in severity was significant in both SUI and MUI types, from the first treatment to the end of the study. Sexual function of patients as reflected in the FSFI questionnaire scores also showed to improve; the difference was significant after the second session (p = 0.013) and persisted at the end of the study (p = 0.047). Conclusion: Fractional, micro-ablative CO2RE Intima laser treatment is a minimally invasive procedure that can significantly improve moderate and severe SUI and MUI. It also improves sexual function in women with these types of incontinence. Though our positive results are promising, this preliminary data must be confirmed with other studies.